Interview: Ancient Hoplitikon, "Poorer Cousin" to History Academia or alternative XXI Century Interpretation of History? - Márta Pócza (EXARC Journal)
I liaise with a number of living history groups globally, which all share the same aims and objectives of researching and actively pursuing experimental archaeology related to Ancient Greece and Rome. By networking, we create a foundation of knowledge that meets our framework for understanding the past, whether it be military martial arts, polytheism, metallurgy, clothing, food and wine or even ancient dialects. A few living history groups do an enormous variety of research and set the standards and benchmarks for the rest to follow! Other groups try to keep up, but are set back due to their budgets and members stagnating in this endeavour. In general the ancient re-enactment movement continues methodically to move forward and bares fruit through recognition from academic institutions and museums. Indeed while we are at the antipodes to Europe and in Australia we are separated by distance, we have a unique style and hope to introduce it to our European colleges!